Cancellation of Executive Stock Options: Tax and Accounting Income Considerations* - Mawani, Amin (Contemporary Accounting Research, 2003)
Canadian firms face a trade‐off between reporting higher accounting income and paying lower taxes that arises from their ability to cancel in‐the‐money executive stock options and making a substitute cash payment to the executive instead of issuing shares. Firms' trade‐off hypotheses are operationalized in a multilateral framework and empirically tested using insider‐trading data. The multilateral approach is designed to control for the incentive effects of alternative compensation schemes and to determine the cancellation payment that keeps the executive indifferent between receiving cash or shares. The results show that firms consider both taxes and financial reporting costs in determining their option cancellation behavior.